Characteristics and quality of life of nine-year survivors with metastatic melanoma treated with pembrolizumab beyond second-line therapy - Dugas-Breit, Susanne; Forschner, A.; Erdmann, M.; Gutzmer, R.; Kähler, K. C.; Holst, I.; Brekner, A.; Franklin, C.; Sindrilaru, A.; Zimmer, L.; Heinzerling, L.; Utikal, Jochen; et al. (European journal of cancer, 2026)
Background - Immune checkpoint blockers have improved survival in metastatic melanoma. Long-term quality of life (QoL) and sequelae from immune-related adverse events (irAE) are therefore of increasing importance. This study reports long-term outcomes from a real-world cohort of patients with stage IV melanoma treated with pembrolizumab after progression on ipilimumab and, if indicated, BRAF/MEK inhibition. - Methods - Survival of patients who started treatment with pembrolizumab within the German Expanded Access Program (EAP) were evaluated in Cancer centers that included ≥10 patients. For survivors, baseline characteristics, best response and irAEs were assessed retrospectively. In addition, in a cross-sectional approach patients were interviewed for persisting symptoms and QoL (WHO-5, EORTC QLQ-C30). - Results - Of 325 treated patients, 55 (17%) survived after a median follow-up of 9.1 years. At treatment start, survivors had a median age of 60 years; 60% were male; 40% BRAF-mutated; 66% stage M1c/d. Overall response rate was 89%, including 69% complete responses. Progression occurred in 22 (40%). As of May 2024, 46 (84%) were disease-free, 7 (13%) had controlled disease, and 2 (4%) progressed. IrAEs occurred in 39 (71%), with 15 (27%) grade 3/4. Persisting symptoms were reported by 19 (35%), mainly endocrine insufficiencies, vitiligo, and fatigue. Median WHO-5 score was 76%, and mean QLQ-C30 global health 70.1. Survivors with prior irAEs had significantly lower QoL (WHO-5, p=0.026) and social functioning (QLQ-C30, p=0.046). Of 21 survivors <65 years (38%), 11 (20%) were employed at follow-up. - Conclusion - Pembrolizumab induced long-term survival in a real-world pretreated melanoma cohort. Despite persisting symptoms in one third, QoL, when measured by standard instruments, was good for most survivors nearly a decade after treatment.
Online verfügbar: 29. November 2025, Artikelversion: 11. Dezember 2025
Gesehen am 16.02.2026